Pengaruh literasi keuangan, nilai pribadi dan sikap terhadap perencanaan keuangan keluarga di Surabaya - Fakhriyah Arfianti Saputri; Iramani Iramani (Journal of Business & Banking, 2019)
The purpose of this research is to determine the influence of financial literacy, personal values, and attitudes of family financial planning in Surabaya. Total of respondents from this research are 115 respondents with the criteria as a manager of family finances, and have a family income at least Rp. 4.000.000 / month, and domiciled in Surabaya city. The analysis technicall used in this research is multiple linear regression analysis. The results explain that financial literacy, personal values, and attitudes have a significant positive effect on family financial planning in Surabaya